A review of patient-reported outcome measures to assess female infertility-related quality of life - Kitchen, Helen (Health Qual Life Outcomes, 2017)
BACKGROUND: Infertility has a negative impact on quality of life (QoL) and well-being of affected individuals and couples. A variety of patient-reported outcome (PRO) measures to assess infertility-related QoL are available; however, there is a concern regarding potential issues with their development methodology, validation and use. This review aimed to i) identify PRO measures used in infertility interventional studies ii) assess validation evidence to identify a reliable, valid PRO measure to assess changes in QoL or treatment satisfaction in clinical studies with female patients following treatment with novel therapies iii) identify potential gaps in evidence for validity. METHODS: A structured literature search of Medline, Embase, and the Cochrane Library (accessed in September 2015) was conducted using pre-defined search terms. The identified publications were reviewed applying eligibility criteria to select interventional female infertility studies using PROs. Infertility-specific PRO measures assessing QoL, treatment satisfaction or psychiatric health, and included in studies by ≥2 research groups were selected and critically reviewed in light of scientific and regulatory guidance (e.g. FDA PRO Guidance for Industry) for evidence of content validity, psychometric strength, and patient acceptability. RESULTS: The literature search and hand-searching yielded 122 publications; 78 unique PRO measures assessing QoL, treatment satisfaction or psychiatric health were identified. Five PRO measures met the selection criteria for detailed review: Fertility Quality of Life (FertiQoL); Fertility Problem Inventory (FPI); Fertility Problem Stress (FPS); Infertility Questionnaire (IFQ); Illness Cognitions Questionnaire adapted for Infertility (ICQ-I). None of the PRO measures met all validation criteria. The FertiQoL was the most widely used infertility-specific PRO measure to assess QoL in interventional studies, with reasonable evidence for adequate content validity, psychometric strength, and linguistic validation. However, gaps in evidence remain including test-retest reliability and thresholds for interpreting clinically important changes. While the FPI demonstrated reasonable evidence for content and psychometric validity, its utility as an outcome measure is limited by a lack of recall period. CONCLUSION: The FertiQoL and the FPI are potentially useful measures of infertility-related QoL in interventional studies. Further research is recommended to address gaps in evidence and confirm both PRO measures as reliable assessments of patient outcomes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12955-017-0666-0) contains supplementary material, which is available to authorized users.